Inhibition of Neutrophil Collagenase/MMP-8 and Gelatinase B/MMP-9 and Protection against Endotoxin Shock - Zheng Qiu; Jianghai Chen; Hanmei Xu; Philippe E. Van den Steen; Ghislain Opdenakker; Min Wang; Jialiang Hu (Journal of Immunology Research)
Endotoxin shock is a life-threatening disorder, associated with the rapid release of neutrophil enzymes, including neutrophil collagenase/matrix metalloproteinase-8 (MMP-8) and gelatinase B/matrix metalloproteinase-9 (MMP-9). After activation, these enzymes cleave extracellular matrix components and cytokines and thus may contribute to shock syndrome development. MMP inhibitors have been suggested as immunotherapy of endotoxin shock. However, little is known about the therapeutic time window of MMP inhibition. Here, a sublethal endotoxin shock mouse model was used to evaluate the effect of an MMP inhibiting peptide (P2) after intravenous or intraperitoneal injection and to study the time window between LPS and inhibitor injections. With the use of a specific ELISA the plasma P2 concentrations were monitored. Whereas we corroborated the treatment strategy of MMP targeting in endotoxin shock with a new inhibitor, we also demonstrated that the time window, within which effective MMP inhibition increased the survival rates, is rather limited.